Comparative Study of the Length-Weight Relationships of Some Fish Species along the Turkish Coasts - GÜNDOĞDU, S.; BAYLAN, M.; ÇEVIK, C. (Mediterranean Marine Science, 2015)
This study presents 738 length-weight relationships for 242 species found in Turkish seas. All length-weight relationships presented were collected from a total of 33 studies. These studies were all performed in Turkish coastal waters between 1997 and 2013. For all studies, the median of a value was calculated as 0.014 and the median of b value was calculated as 3.016.